PROSODI SEMANTIK SINONIM KATA “LAKI-LAKI” DAN “PRIA” DALAM WACANA-WACANA DI INTERNET: STUDI LINGUISTIK KORPUS - Rahma, Nurul Na’imahtul (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2025)
This study aims to describe the distribution pattern of the words "laki-laki" and "pria" in three types of discourse, namely news discourse, website discourse, and Wikipedia discourse uploaded on the internet. In addition, this study also aims to look at the semantic prosody or positive, negative, or neutral tendencies of the words collocated with the words "laki-laki" and "pria". This research uses a combined research method (mix method). To find out the distribution pattern of the use of the words “laki-laki” and “pria”, this study uses data sources from LCC Indonesian 2023 (Leipzig Corpora Collection) and uses the CQPWeb corpus analysis instrument, and is analysed with the theoretical approach of semantic prosody. The results show that in the three types of discourse uploaded on the internet, the word "pria" is used more than the word "laki-laki". Then, the words "laki-laki" and "pria" have close collocation with the words "lain", “tua”, “muda”, and "dewasa". The results also show that the words "laki-laki" and "pria" in the collection of discourses uploaded on the internet have similar collocation behaviour and have positive semantic prosody.